Strategi Efektif Penerapan Inkubator Bisnis Terhadap Perusahaan Startup di Indonesia - Ramadian, Afzil; Hariyadi , Mursidi; Fairuz, Rozaan; Rabbani, Rafi (Indonesian Journal Publisher, 2024)
This research aims to examine the potential impact of business incubators on startups in Indonesia. Using a descriptive qualitative method and library research, the study investigates how business incubators contribute to the development of startups by providing access to essential resources, networks, and mentors. The findings reveal that business incubators play a crucial role in helping startups overcome early-stage challenges and achieve sustainable growth. They facilitate collaboration with artists, designers, and other cultural practitioners, thereby enhancing the creative and innovative capabilities of startups. The study underscores the necessity for the government and private sector to collaborate in establishing more high-quality and sustainable business incubators to bolster the startup ecosystem in Indonesia. The conclusion highlights the significant potential of business incubators in fostering startup success through the provision of capital, mentorship, and other critical resources. The research suggests that cross-sector cooperation is essential for maximizing the impact of business incubators. Although the study acknowledges certain limitations, the findings provide valuable insights for the development of the startup ecosystem in Indonesia and lay the groundwork for further research and innovation.